Marketing management - Clow, Kenneth E (Sage, 2010)
Includes bibliographical references and index; The nature of marketing management -- Market analysis -- Scooping up success -- Data warehousing : majestic mountain ski resort -- Building a customer-oriented marketing department : the new boss -- Customer acquisition strategies and tactics : lenscrafters -- Pricing : that's how the cookie crumbles -- Advertising, alternative, and direct marketing : wild West rodeo -- Sales promotions